Trait evolution in the slipper orchid paphiopedilum (Orchidaceae) in China. (3rd March 2016) - Zhang, Feng-Ping; Huang, Jia-Lin; Zhang, Shi-Bao
ABSTRACT: The well-known orchid genus Paphiopedilum has attracted much attention from biologists because of its diverse floral traits. Although these traits have been thoroughly described, little is known about their evolutionary trajectory. In this study, we explored their evolutionary patterns and trajectory through phylogenetic analyses and close observations, and 10 characters in 21 Chinese species mapped onto an existing phylogenetic tree. Lip shape, staminode shape, petal shape, and petal width are relatively congruent with molecular phylogenies, thereby validating the existing traditional classification system. All four of those characters, along with flower number, are strongly conserved, and are significantly affected by phylogeny. By contrast, flower color (including that of the dorsal sepal, lip, and petal) is significantly convergent among those examined species and less affected by phylogeny. Therefore, this character is independent of evolution and mainly influenced by environmental factors. All of these characters are key, classical indicators when distinguishing among species within the subgenera Brachypetalum and Paphiopedilum.